Analisis Uji Validitas Job sheet Praktikum Mekatronika 2 Berbasis Problem-Based Learning di Pendidikan Vokasi - Dedek Rahmat; Juli Sardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study discusses one of the stages of research on the development of Problem-Based Learning Mechatronics 2 practicum job sheet for the learning process of Mechatronics Practicum 2 students of the Electrical Engineering Department, namely validity testing analysis. The validity of the Problem-Based Learning -based Mechatronics 2 practicum job sheet is divided into two aspects, namely media and material aspects. Each aspect is validated respectively by two validators who have expertise in accordance with these aspects. The instrument used in this validity test is a validity questionnaire that has gone through the instrument validation process before. The analysis was carried out with Aiken's V validity analysis technique. Then it was interpreted with the product development validity interpretation table to get the validity category. The results showed that the Problem-Based Learning -based Mechatronics 2 practicum job sheet developed was valid in all aspects of both media and material aspects. The media aspect obtained a value of V = 0.93 which means valid, and the material aspect obtained a value of V = 0.9 with a valid category. Thus, it can be concluded that the Problem-Based Learning -based Mechatronics 2 practicum job sheet developed for the learning process of Mechatronics 2 Practicum for Electrical Engineering Department students is valid in both media and material aspects.